Prediction of localization and interactions of apoptotic proteins - Varecha, Miroslav; Zimmermann, Michal; Amrichová, Jana; Ulman, Vladimír; Matula, Pavel; Kozubek, Michal (Journal of biomedical science, 2009)
During apoptosis several mitochondrial proteins are released. Some of them participate in caspase-independent nuclear DNA degradation, especially apoptosis-inducing factor (AIF) and endonuclease G (endoG). Another interesting protein, which was expected to act similarly as AIF due to the high sequence homology with AIF is AIF-homologous mitochondrion-associated inducer of death (AMID). We studied the structure, cellular localization, and interactions of several proteins in silico and also in cells using fluorescent microscopy. We found the AMID protein to be cytoplasmic, most probably incorporated into the cytoplasmic side of the lipid membranes. Bioinformatic predictions were conducted to analyze the interactions of the studied proteins with each other and with other possible partners. We conducted molecular modeling of proteins with unknown 3D structures. These models were then refined by MolProbity server and employed in molecular docking simulations of interactions. Our results show data acquired using a combination of modern in silico methods and image analysis to understand the localization, interactions and functions of proteins AMID, AIF, endonuclease G, and other apoptosis-related proteins.
Keywords: biologické modely; apoptóza; Caspases; Microscopy, Fluorescence; Cell Line, Tumor; endonukleasy; Protein Structure, Tertiary; počítačová simulace; Apoptosis; vazba proteinů; Endonucleases; software; terciární struktura proteinů; lidé; Models, Biological; proteomika; fluorescenční mikroskopie; Computer Simulation; Models, Molecular; Proteomics; Computational Biology; Protein Conformation; molekulární modely; konformace proteinů; Software; kaspasy; výpočetní biologie; Protein Binding; nádorové buněčné linie; Humans